2020
DOI: 10.7717/peerj.9033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and structure of an important wild steppe grass Psathyrostachys juncea (Triticeae: Poaceae) germplasm collection from north and central Asia

Abstract: Russian wildrye, Psathyrostachys junceus (Fisch.) Nevski, is an important wild steppe perennial grass, which is characterized by longevity and short robust rhizomes. It also has highly resistance in grazing and abiotic stress. In this study, the genetic diversity of eleven P. juncea wild germplasms from north and central Asia was investigated using AFLP markers. The P. juncea populations were divided into three clades in both UPGMA dendrogram and PCoA clustering corresponding to the three genetic memberships i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(62 reference statements)
2
3
0
Order By: Relevance
“…Genetic variation within the populations (83-93%) was higher than that among populations (5-7%) in the present study. This result is consistent with the findings of previous studies of P. juncea based on AFLP analysis (77% within populations) (Xiong et al, 2020), Black cottonwood (Populus deltoides) based on SSR (84.88% within individuals) (Chen et al, 2020), white clover based on AFLP analysis (84% within cultivars) (Kölliker et al, 2001) and white clover based on SSR (86.5% within cultivars) (George et al, 2006). This is also consistent with the results of studies on other cross pollinating species, such as perennial ryegrass (Bolaric et al, 2005;Van Treuren et al, 2005).…”
Section: Genetic Variation Of Psathyrostachys Juncea Materials and Ge...supporting
confidence: 93%
See 2 more Smart Citations
“…Genetic variation within the populations (83-93%) was higher than that among populations (5-7%) in the present study. This result is consistent with the findings of previous studies of P. juncea based on AFLP analysis (77% within populations) (Xiong et al, 2020), Black cottonwood (Populus deltoides) based on SSR (84.88% within individuals) (Chen et al, 2020), white clover based on AFLP analysis (84% within cultivars) (Kölliker et al, 2001) and white clover based on SSR (86.5% within cultivars) (George et al, 2006). This is also consistent with the results of studies on other cross pollinating species, such as perennial ryegrass (Bolaric et al, 2005;Van Treuren et al, 2005).…”
Section: Genetic Variation Of Psathyrostachys Juncea Materials and Ge...supporting
confidence: 93%
“…The Mantel test of genetic distance and geographical distance among materials showed that there was a significant correlation ( R 2 = 0.0269, P = 0.025). This showed an IBD model over all sampling locations that was comparable with the results of Xiong et al’s (2020) research, which analyzed the genetic diversity of eleven P. juncea wild germplasms using AFLP markers, and identified that the key factors inducing moderate genetic differentiation were isolation by distance (IBD). Generally, more opportunity for allelic exchange could be obtained by individuals of neighboring populations because gene flow will theoretically be obstructed by a longer geographical distance ( Zhang et al, 2018 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the high level of diversity within clusters observed in this study agrees with patterns of genetic diversity found in other grass species. For example, Xiong et al [ 33 ] analyzed the genetic diversity of the grass Psathyrostachys junceain and found that most of the variation (87.6%) occurred within populations. Similar results were found by Wu et al [ 34 ], who reported that the genetic differences among populations of Elymus tangutorum explained 26.1% of the global variation.…”
Section: Discussionmentioning
confidence: 99%
“…1a). We assessed the individual proportion membership (qi) in the groups using the threshold value of 0.8, as used in other grass species; individuals with a value of ≥0.8 were considered to have a strong affinity to a group, and those with < 0.80 as an admixture [31][32][33][34]. With the threshold value of qi ≥0.80, the structure at K = 2 revealed two groups (S1 and S2; Fig.…”
Section: Genetic Structurementioning
confidence: 99%